Fuckhead - Rawson, David (punctum books, 2013)
What is a fuckhead? David Rawson's Fuckhead is a surreal exploration of the literature, film, nature and expectations of disability, and of fuckheads in literature and film. Part lyric essay, part fictional memoir, Rawson's work tells the story of an unnamed narrator whose familial relationships are defined by his VATER syndrome. Abused by his mother and stripped of a voice by his brother's need to be Tom Cruise via Rain Man, he sets out into a universe of literary tropes. I have always been of the mind that the novelist is allowed access to all experiences, as long as he ultimately has something to say. Plutarch and Samuel Johnson are typing somewhere in the desert of the next world, composing the ultimate collection of biographical criticism, explaining how David Lynch's entire filmography owes a debt to his club feet. But I and the friends who bought my novel agree the author is dead. The work is particularly interested in the relationship between Steinbeck's Of Mice and Men and what the narrator argues is Denis Johnson's reimagining of that work in the short story "Emergency" (in Johnson's Jesus' Son). But in accumulating characters with disabilities as widely diverse as Darth Vader, Benjy of Faulkner's The Sound and the Fury, and the TV sitcom Community's Abed Nadir, Rawson movingly, and with wry humor, articulates the assumptions and clichés faced by persons with disabilities, all the while creating a new family with his unlikely gathering of "fuckheads."